Glycyrrhizic Acid Mitigates Tripterygium-Glycoside-Tablet-Induced Acute Liver Injury via PKM2 Regulated Oxidative Stress - Wang, Qixin; Huang, Yuwen; Li, Yu; Zhang, Luyun; Tang, Huan; Zhang, Junzhe; Cheng, Guangqing; Zhao, Minghong; Lu, Tianming; Zhang, Qian; Luo, Piao; Zhu, Yinhua; et al. (Metabolites, 2022)
Tripterygium glycoside tablet (TGT), as a common clinical drug, can easily cause liver damage due to the narrow therapeutic window. Glycyrrhizic acid (GA) has a hepatoprotective effect, but the characteristics and mechanism of GA’s impact on TGT-induced acute liver injury by regulating oxidative stress remain unelucidated. In this study, TGT-induced acute liver injury models were established in vitro and in vivo. The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (AKP), superoxide dismutase (SOD), malondialdehyde (MDA), glutathione (GSH), catalase (CAT), lactate dehydrogenase (LDH), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) were quantified. The anti-apoptotic effect of GA was tested using flow cytometry. Potential target proteins of GA were profiled via activity-based protein profiling (ABPP) using a cysteine-specific (IAA-yne) probe. The results demonstrate that GA markedly decreased the concentrations of ALT, AST, AKP, MDA, LDH, TNF-α, IL-1β and IL-6, whereas those of SOD, GSH and CAT increased. GA could inhibit TGT-induced apoptosis in BRL-3A cells. GA bound directly to the cysteine residue of PKM2. The CETSA and enzyme activity results validate the specific targets identified. GA could mitigate TGT-induced acute liver injury by mediating PKM2, reducing oxidative stress and inflammation and reducing hepatocyte apoptosis.